Biologian aineenopettajaopiskelijoiden asenteet ja valmiudet opettaa genetiikkaa - Ihamäki, Outi; Kostamo, Emilia (2013)
Genetics is a relevant topic in modern society and its applications are widely used in everyday life as well as in scientific research. As the goal of general education is to give students the abilities needed to be a member of society, genetics is also part of secondary school and upper secondary school biology teaching. Teachers think that teaching genetics in school is important. However genetics is viewed as a difficult subject to learn. Although students’ skills in genetics have been measured in studies, there are no skill rate measurement tests extended to teachers and teacher students. However, teachers’ knowledge of the subject influences students’ learning results, and so, in order for Finnish education to continue being of high quality, research must take teacher training into account as well. The aim of this study was to observe the attitudes and abilities of teacher students of biology to teach genetics. We also tried to find out what these student teachers think about their own abilities to teach genetics, and whether they think that university education has offered adequate tools for working life. The study material consists of interviews with 19 participants who are in teacher training in biology through both major and minor studies in the subject. As research methods interviewing and a test that measured skills in genetics were used. In this study we found that student teachers thought that genetics is interesting, but they did not find it a difficult subject to learn. The more interesting the subject of genetics was perceived, the easier its learning was. The study also showed that the motivation in the interviewees to both teach and study genetics was high. There was a positive correlation between the experienced necessity of knowing genetics and the teaching motivation of the subject. However, there was no correlation between the evaluation of the student teachers’ own abilities and the results of the genetics test. The student teachers found the study of genetics at the university useful. Still, they thought that more courses directed to student teachers, and which would consist of practical information and dealing with the possible problem areas of teaching genetics would be useful. It is necessary to do further and more extensive research on the problem areas of genetics and the effects of teachers' attitudes and motivation on pupils’ learning results. Especially Finnish studies about this subject would be important, because foreign studies do not directly match the situation in Finland because of the differences between education systems.